2015
DOI: 10.3389/fnins.2015.00415
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neural structure and function contributing to autonomic symptoms in congenital central hypoventilation syndrome

Abstract: Congenital central hypoventilation syndrome (CCHS) patients show major autonomic alterations in addition to their better-known breathing deficiencies. The processes underlying CCHS, mutations in the PHOX2B gene, target autonomic neuronal development, with frame shift extent contributing to symptom severity. Many autonomic characteristics, such as impaired pupillary constriction and poor temperature regulation, reflect parasympathetic alterations, and can include disturbed alimentary processes, with malabsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 83 publications
(137 reference statements)
3
26
0
2
Order By: Relevance
“…Our findings suggest that the adverse neurocognitive impact of CCHS may be even broader than previous studies have suggested, emphasizing the importance of early identification and conservative management. Our data also complement a rapidly growing body of brain imaging research in CCHS providing clear evidence of structural and functional abnormalities of brain systems involved in autonomic regulation . Our findings urge caution in the design and interpretation of research on neurocognitive functioning in rare disease clinical populations such as CCHS relative to general population norms, and emphasize the importance of controls matched as nearly as possible on socioeconomic, situational, and other non‐disease‐related heritable factors in studies of pediatric neurocognitive outcome.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our findings suggest that the adverse neurocognitive impact of CCHS may be even broader than previous studies have suggested, emphasizing the importance of early identification and conservative management. Our data also complement a rapidly growing body of brain imaging research in CCHS providing clear evidence of structural and functional abnormalities of brain systems involved in autonomic regulation . Our findings urge caution in the design and interpretation of research on neurocognitive functioning in rare disease clinical populations such as CCHS relative to general population norms, and emphasize the importance of controls matched as nearly as possible on socioeconomic, situational, and other non‐disease‐related heritable factors in studies of pediatric neurocognitive outcome.…”
Section: Discussionsupporting
confidence: 61%
“…Neuropathology evaluation of young infants with CCHS indicates anatomic alterations that may translate to reduced neurological outcomes . Neuroimaging studies of adolescents with CCHS have provided clear evidence of structural and functional abnormalities of brain systems involved in autonomic regulation that might result in altered neurological outcomes . A report of Japanese infants with CCHS who had delayed diagnosis and management with supplemental oxygen rather than tracheostomy/artificial ventilation in the newborn period indicates the impact of postnatal physiologic compromise on neurocognitive outcome especially when compared with our report in preschool children with CCHS…”
Section: Discussionsupporting
confidence: 48%
“…It is worth noting that the role of PHOX2B in adulthood has not been investigated, although in mice Phox2b expression persists in most brainstem structures after birth . Together with the findings that brain imaging and functional magnetic resonance imaging (fMRI) studies of CCHS patients suggest that other damages occur progressively, in addition to the developmental defects induced by PHOX2B mutations , we cannot exclude a role for fibrils in CCHS ‘progression’. This evidence could pave the way for an innovative rational design of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 82%
“…The posterior thalamus plays a significant role in oxygen sensing [28] and in relaying afferent activity essential for breathing [12]. A disruption of the thalamic-brain stem link in high-risk SUDEP patients is particularly worrisome due to its involvement with respiratory failure in SUDEP.…”
Section: Mechanismsmentioning
confidence: 99%